Social determinants of health associated with childhood accidents at home: An integrative review - Ribeiro,Márcia Gabriela Costa (2019)
ABSTRACT Objective: to analyze the factors associated with childhood accidents at home according to the levels of the social determinants of health. Method: integrative review of the literature, with research in databases CINAHL, LILACS and PubMed, with the following main descriptors: child; social determinants of health; accidentes, home. We included 31 studies that related the social determinants of health and childhood accidents, in English, Portuguese and Spanish. Results: the proximal determinants identified were: age and sex of children, and ethnicity. Among the intermediate determinants of health, parental behavior, related to the supervision of an adult, prevailed. Parental employment and socioeconomic status were identified as distal determinants. Conclusion: the age and sex of the child, besides direct supervision, were the determinants most associated with accidents. The distal determinants should be better studied because their relation with the occurrence of domestic accidents has not been sufficiently clarified.